TF-Test Quantified: a new technique for diagnosis of Schistosoma mansoni eggs - Santos, Bianca Martins; Soares, Felipe Augusto; Rosa, Stefany Laryssa; Ferreira Gomes, Denise da Conceicao; Miranda Oliveira, Bruno Cesar [UNESP]; Peixinho, Alan Zanoni; Nagase Suzuki, Celso Tetsuo; Saraiva Bresciani, Katia Denise [UNESP]; Falcao, Alexandre Xavier; Gomes, Jancarlo Ferreira (Wiley-Blackwell, 2019)
objectives Laboratory diagnosis of Schistosoma mansoni eggs is routinely performed by conventional quantitative techniques through the parasitological examination of human faeces. However, the diagnostic sensitivity of this type of exam varies from low to moderate. We aimed to develop a new parasitological technique called TF-Test Quantified (TFT-Quant), for the quantitative detection of S. mansoni eggs in human faeces. methods Four study stages were performed using 43 mice infected by S. mansoni cercariae. These experiments allowed the definition of an operational protocol for TFT-Quant and a comparison of this new technique to the conventional Helm-Teste technique. results The results show a good diagnostic efficacy of TFT-Quant, which reached 100% in sensitivity and specificity, indicating an ` Almost Perfect' Kappa (k) agreement. conclusions This new technique provided a quantitative gain in the detection of S. mansoni eggs, largely free of faecal debris. The next stage of this study is the field validation of the TFT-Quant technique with the use of human faecal samples from an endemic region for mansonic schistosomiasis in Brazil (Microregion Jequitinhonha, State of Minas Gerais). In parallel to this validation, computational algorithms will be developed to allow the automated quantitative diagnosis of S. mansoni eggs.
Keywords: TFT-Quant; laboratory diagnosis; Schistosoma mansoni